External indicators of fisheries interactions in known bycaught dolphins from bather protection nets along the KwaZuluNatal coastline, South Africa - Roussouw, Natasha; Wintner, Sabine; Hofmeyr, Greg; Wohlsein, Peter; Siebert, Ursula; Plön, Stephanie (J. Cetacean Res. Manage., 2022)
Detailed examinations of dolphins incidentally caught in bather protection nets along the KwaZulu‐Natal coastline, South Africa, over the past 10 years have yielded a dataset that can assist in the examination of external signs of bycatch. Investigating these external signs of fisheries interactions could aid in determining whether they could be used as unequivocal indicators of entanglement in stranded dolphins for which cause of death is unknown. The aim of this study was to investigate the occurrence of netmarks and other external injuries on individuals of two dolphin species (Tursiops aduncus and Sousa plumbea), both bycaught and stranded, along the south‐east coast of South Africa. Necropsy reports and photographs of 107 bycaught and 15 stranded dolphins between 2010 and 2017 were investigated to determine prevalence of netmarks and other external injuries in relation to species, sex, age class, and water temperature. Our results indicated that 36% of the bycaught dolphins and 13% of stranded dolphins showed netmarks on the skin. In bycaught animals, females were more likely to show netmarks (58%) and the majority of dolphins with netmarks were immatures (66%; immatures included calves, neonates and subadults). There was little evidence for water temperature affecting the appearance of netmarks. Furthermore, species, sex or age class did not play a significant role in the probability of netmark occurrence. Other external injuries were also observed in the bycaught (3–50%) and stranded animals (7–100%), with subcutaneous bruising being the most prominent sign in bycaught animals. Our study showed that only a small percentage of known bycaught animals actually present external signs of entanglement. Thus, additional evidence, such as histopathological examinations, is required to reliably identify entanglement cases in stranded animals.